2012
DOI: 10.1016/j.bpj.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the N-Terminal Lobe of the Myosin Regulatory Light Chain in Skeletal Muscle Fibers

Abstract: The orientation of the N-terminal lobe of the myosin regulatory light chain (RLC) in demembranated fibers of rabbit psoas muscle was determined by polarized fluorescence. The native RLC was replaced by a smooth muscle RLC with a bifunctional rhodamine probe attached to its A, B, C, or D helix. Fiber fluorescence data were interpreted using the crystal structure of the head domain of chicken skeletal myosin in the nucleotide-free state. The peak angle between the lever axis of the myosin head and the fiber or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 35 publications
14
16
0
Order By: Relevance
“…2A). We found that smRLC, used in previous studies , reports similar orientation compared to skRLC, consistent with previous results (Romano et al, 2012).…”
Section: Summary Of Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…2A). We found that smRLC, used in previous studies , reports similar orientation compared to skRLC, consistent with previous results (Romano et al, 2012).…”
Section: Summary Of Resultssupporting
confidence: 92%
“…Fig. 2B shows that orientations of smRLC and skRLC are hardly distinguishable, which is consistent with fluorescence polarization experiments (Romano et al, 2012). Therefore, to maximize the physiological relevance of our work, we focused on skRLC from here on.…”
Section: Detecting Anisotropy In the Epr Fiber Experiments And Rlc Homsupporting
confidence: 85%
See 3 more Smart Citations